2013
DOI: 10.1139/cjfas-2012-0246
|View full text |Cite
|
Sign up to set email alerts
|

Invasive male round gobies (Neogobius melanostomus) release pheromones in their urine to attract females

Abstract: The round goby (Neogobius melanostomus) is an invasive fish in the Laurentian Great Lakes and beyond. Pheromones appear to be important for their reproductive success, as females are attracted to water in which reproductive males have resided ("conditioned water"). Previous investigation has shown conjugated and unconjugated forms of 3␣-hydroxy- are released in the urine of these males. The goal of this study was to determine if the urine of reproductive males and fractionated extracts attract females. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…A similar observation was made of African catfish (Clarias gariepinus) males, where the most potent testicular odorant was found to be 20one-P-3-G (Lambert and Resink, 1991). Androstanes and pregnanes with a 5β,3α configuration are also potent odorants for the round goby (Neogobius melanostomus, Pallas 1814) (Murphy et al, 2001), and recent studies have demonstrated that round goby males release several conjugated forms of these steroids via their urine (Katare et al, 2011), eventually to attract females (Tierney et al, 2013). However, in the round goby, the olfactory receptors detecting ETIO-3-G appear to be less specific than those in tilapia; several unconjugated androstanes, pregnanes and even androsten, are detected by the same (ETIO-3-G) receptor site (Murphy et al, 2001).…”
Section: Binary Mixture Testssupporting
confidence: 58%
See 1 more Smart Citation
“…A similar observation was made of African catfish (Clarias gariepinus) males, where the most potent testicular odorant was found to be 20one-P-3-G (Lambert and Resink, 1991). Androstanes and pregnanes with a 5β,3α configuration are also potent odorants for the round goby (Neogobius melanostomus, Pallas 1814) (Murphy et al, 2001), and recent studies have demonstrated that round goby males release several conjugated forms of these steroids via their urine (Katare et al, 2011), eventually to attract females (Tierney et al, 2013). However, in the round goby, the olfactory receptors detecting ETIO-3-G appear to be less specific than those in tilapia; several unconjugated androstanes, pregnanes and even androsten, are detected by the same (ETIO-3-G) receptor site (Murphy et al, 2001).…”
Section: Binary Mixture Testssupporting
confidence: 58%
“…Within the Perciformes, the largest teleost order (Order Summary for Perciformes, www.fishbase.org), studies on olfactory sensitivity to, and pheromonal function of, hormonal steroids are scarce and derive from a few representatives of the Gobiidae (Colombo et al, 1980;Corkum et al, 2008;Murphy et al, 2001;Tierney et al, 2013) and Cichlidae (Cole and Stacey, 2006;Hubbard et al, 2014;KellerCosta et al, 2014). Cichlids are an extremely diverse taxon with currently 1670 described species ('List of Nominal Species of Cichlidae', www.fishbase.org), mostly native to Africa, and adaptation of the sensory and signalling systems to different environmental conditions has been suggested as an important driver in African cichlid radiation (Seehausen et al, 2008).…”
mentioning
confidence: 99%
“…In addition, the observed cases of gene expansions in receptors warrant investigations into the evolution of ligand binding repertoires. For example, olfactory receptor 7tm1 subfamily members are expanded in Gobiidae, and we hypothesize that they may be involved in the detection of distinctive types of odors relevant for Gobiidae ecology and/or reproduction [31][32][33]. Which types of odorants are detected by parallel expanded ORs, and whether these expansions serve to detect similar or different types of odorant molecules in different species, remain to be studied.…”
Section: Gene Expansionsmentioning
confidence: 98%
“…Similarly, olfaction is an essential chemoreception sense for fish, allowing for fast responses to predators and alarm cues, as well as for intra-species communication. Pheromones play an important role in the round goby [31][32][33], and males attract females into their nests by releasing them [34]. A particularly specialized sense of smell therefore may provide an advantage during initial population establishment in novel environments, when population densities are still low.…”
Section: Introductionmentioning
confidence: 99%